Peran Pengenalan Investasi terhadap Ibu-Ibu PKK Taman Permata Cikunir, Bekasi Selatan - Utami, Novia; Angelia Kusumahadi, Teresia (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program aims to enhance financial and investment literacy among PKK mothers in Taman Permata Cikunir, South Bekasi. Using an educational approach tailored to community needs, the activity involved two main sessions covering basic investment concepts, household financial planning, and the risks of illegal investment schemes. Evaluation was conducted using pre-tests and post-tests to measure program effectiveness. Results showed an average increase of 26% in participants' understanding, with significant improvement in budgeting and investment risk topics. These findings highlight the importance of community-based educational interventions. Improved investment literacy is expected to empower PKK mothers to manage household finances wisely and select appropriate financial instruments. This initiative contributes to women’s economic empowerment and promotes a healthier, more sustainable local financial ecosystem.